A Big Year for Chemistry and Sustainability. Issue 2 (2nd January 2019) - Smith, David J.
Abstract : Looking back and moving forward : ChemSusChem Editor in Chief David Smith looks back on the journal's past twelve months and considers what 2019 holds for sustainable chemistry, with the help of Editorial Board Chairs Matthias Beller, Gabriele Centi, and Licheng Sun.